PERTUMBUHAN SANSEVIERIA PADA KOMPOSISI MEDIA TANAM MENGGUNAKAN TANAH LIMBAH PETI DI KABUPATEN KUANTAN SINGINGI - Zulfikar; Tengku Nurhidayah; Muhammad Ali (UIR Press, 2022)
This study aims to examine the best composition of planting media using PETI (unlicensed gold mining) which is best for the growth of Sansevieria aubritiana 'Tiger' and Sansevieria trifasciata 'Laurentii'. This research was conducted at the greenhouse of the Faculty of the Agriculture University of Riau. The research was carried out experimentally by using a Completely Randomized Design (Factorial) consisting of two factors, the first was plant type (S) and then planting media (M), which consisted of 6 treatments and 3 replications. So that 18 research units were obtained. The treatments consisted of M1S1 (Coffin land + TKKS compost 1:1, type S. aubrytiana 'Tiger'), M2S1 (Coffin land + husk charcoal 1:1, type S. aubrytiana 'Tiger'), M3S1 (Coffin land + TKKS compost + husk charcoal 1:1:1, type S. 'Tiger'), M1S2 (Coffin land + TKKS compost 1:1, type S. trifasciata 'Laurentii'), M2S2 (Coffin land + husk charcoal 1:1, type S. trifasciata 'Laurentii') and M3S2 (Coffin land + TKKS compost + husk charcoal 1:1:1, type S. trifasciata 'Laurentii'). The data obtained were then further tested by Duncan's multiple range test at 5 %. The results of the study concluded that the combination of planting media of Coffin land + husk charcoal 1:1 was to be able to increase height, the number of leaves, leaf length, root volume, and the number of tillers in S. aubrytiana 'Tiger'. The use of a combination of planting media of Coffin land + TKKS compost 1:1 was able to increase height, the number of leaves, leaf length, and leaf width on S. trifasciata 'Laurentii'.